ANALISIS FAKTOR–FAKTOR YANG BERPENGARUH TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2013-2015) - Okky Ishma Khairirina, 14.05.62.0035; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2017)
This research was performed to examine the effect of variable profitability, liquidity, leverage, and firm size on dividend policy by manufacturing companies listed on the Stock Exchange of Indonesia from 2013 to 2015. The profitability as measured by ROA, liquidity as measured by CR, leverage as measured by DER, firm size measured with the natural log of total assets and dividend policy with Devidend Payout Ratio. The population of this research is 147 manufacturing companies listed on the Stock Exchange of Indonesia from 2013 to 2015. The sampling technique used was purposive sampling with specified criteria. Data obtained from the publication official website BEI (www.idx.co.id). Obtained a sample of 33 companies. The analysis technique used is multiple regression. The results of profitability and liquidity has a significant negative relationship with dividend policy. Leverage has not significant negative and firm size has a significant positive relationship with dividend policy.Keywords: Profitability, Liquidity, Leverage, Firm Size, and Dividend Policy